Health risk assessment of potentially toxic elements in Maros karst groundwater: a Monte Carlo simulation approach. Issue 1 (31st December 2022) - Mallongi, Anwar; Rauf, Annisa Utami; Daud, Anwar; Hatta, Muhammad; Al-Madhoun, Wesam; Amiruddin, Ridwan; Stang, Stang; Wahyu, Atjo; Astuti, Ratna Dwi Puji
Abstract: This study investigated potentially toxic elements (PTEs) pollution in groundwater across the Maros karst area. The groundwater quality was evaluated using three indexing methods, the heavy metal pollution index (HPI), the heavy metal evaluation index (HMEI) and the contamination index ( C d ) . The levels of PTEs were calculated to determine the noncancer and cancer risks to the residents through ingestion and dermal adsorption. To obtain high-level accuracy in cancer risk estimation, a Monte Carlo simulation model and sensitivity analysis were performed. The mean values of PTEs in rainy and summer season were followed the order of Cr > Pb > Zn > Cu and Cr > Zn > Pb > Cu, respectively. The high level of Pb and Cr were exceeded the permissible limit of the World Health Organization (WHO) and Indonesian Standards. However, TDS, pH, EC and temperature were still in accordance with WHO guidelines. The geostatistical interpolation of HPI, HMEI and C d revealed that the groundwater quality around Maros karst is low, particularly in Tukamasea and Leang-Leang village. Hazard index values were lower than one, implying no possibility of noncancer risk. The Monte Carlo simulation results with 95% confidence demonstrated children and adults are at risk for developing cancer due to PTE exposure. Graphical Abstract: UF0001